ANALISIS RENCANA ANGGARAN BIAYA PEMBANGUNAN RUMAH TIPE 36 PADA PERUMAHAN DE’CIRCLE SAMARINDA - Mandola, Ramly W Mandola W (EKONOMIA, 2015)
Needs housing company will budget plan is for the company to find out how much it cost to build a house and in addition to the needs of the preparation of financial data is also needed BP consumer installment because most of the development funds based on financial income from the sale of houses, from the above explanation, it can be formulated problem is whether